A Novel TLC Densitometry Method for Simultaneous Quantification of the Newly Co-formulated Antimicrobial Agents Minocycline, Ciprofloxacin and Metronidazol - معروف محمد; الحاج صكر أمير; قواس غفران (Latakia University Journal -Basic Sciences Series, 2021)
A newly approved Antibiotics mixture (combination) of minocycline (MIN), ciprofloxacin HCl (CIP) and metronidazole (MET), has been used for dental root canal medicaments in pulp regeneration therapy. It is necessary to developing analytical method for the new drug combination. In the present work; an accurate, precise and simple thin-layer chromatography densitometry method (TLC – densitometry) has been developed for simultaneous determination of MET, CIP and MIN in their laboratory made dosage form. The proposed method based on determination of the UV-visualized bands after TLC separation of MET, CIP and MIN. The studied drugs were quantitatively separated on Merck aluminum TLC plates covered with silica gel 60 F254 plates (20 × 20 cm) as stationary Phase, using mobile phase consists of (acetonitrile:methanol:H2O:ammonia:dichloromethane) (25:42:4:12:17)v/v. Densitometric scanning of the separated spots was done at 220 nm. with UV detection. This chromatographic system results in symmetric, compact peaks at Rf values of 0.208 ±0.003, 0.454 ±0.004 and 0.841 ±0.004 for MIN, CIP and MET, respectively. The proposed method has been validated according to the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) guidelines. The proposed method can quantitatively analyze MIN, CIP and MET in their laboratory prepared combinations without interference from excipients. The suggested method is novel, rapid, accurate, reproducible and of low cost, so; thus, it can be used for quality control analysis of these formulations.